2019
DOI: 10.1002/hep.30662
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte‐Derived Exosomal Long Noncoding RNA H19 Promotes Hepatic Stellate Cell Activation and Cholestatic Liver Fibrosis

Abstract: Activation of hepatic stellate cells (HSCs) represents the primary driving force to promote the progression of chronic cholestatic liver diseases. We previously reported that cholangiocyte-derived exosomal long noncoding RNA-H19 (lncRNA-H19) plays a critical role in promoting cholestatic liver injury. However, it remains unclear whether cholangiocyte-derived lncRNA-H19 regulates HSC activation, which is the major focus of this study. Both bile duct ligation (BDL) and Mdr2 knockout (Mdr2 -/-) mouse models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
145
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 45 publications
(59 reference statements)
1
145
0
1
Order By: Relevance
“…Lipotoxic hepatocyte‐derived EVs induced inflammatory responses such as IL‐1β and IL‐6 production in macrophages by delivering cargo TRAIL . Another study has demonstrated that cholangiocytes secrete EVs that contain elevated levels of lncRNA H19 during cholestatic liver injury, and these H19‐enriched EVs activates HSCs leading to liver fibrosis in cholangiopathies …”
Section: Therapeutic Potentials Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipotoxic hepatocyte‐derived EVs induced inflammatory responses such as IL‐1β and IL‐6 production in macrophages by delivering cargo TRAIL . Another study has demonstrated that cholangiocytes secrete EVs that contain elevated levels of lncRNA H19 during cholestatic liver injury, and these H19‐enriched EVs activates HSCs leading to liver fibrosis in cholangiopathies …”
Section: Therapeutic Potentials Of Extracellular Vesiclesmentioning
confidence: 99%
“…104 Another study has demonstrated that cholangiocytes secrete EVs that contain elevated levels of lncRNA H19 during cholestatic liver injury, and these H19-enriched EVs activates HSCs leading to liver fibrosis in cholangiopathies. 105 EVs mediate inflammatory or fibrogenic responses in hepatic cells by delivering cargo mediators, which means that EVs could be used as therapeutic tools or drug carriers to regulate functions of cells by delivering mediators to maintain homeostasis during liver diseases. 106 For example, EVs secreted from liver stem cells contained elevated levels of miRNA let-7a, and injection of stem cell-derived EVs ameliorated ductular reaction and liver fibrosis in Mdr2 −/− mice by delivering cargo let-7a.…”
Section: Associated Disease Modelmentioning
confidence: 99%
“…Liver fibrosis is a frequent consequence of liver injury and can progress to cirrhosis and even hepatocarcinoma. Activation of hepatic stellate cells (HSCs)—transdifferentiation of quiescent, vitamin‐A‐storing cells into proliferative, fibrogenic myofibroblasts—is a prominent driver of liver fibrogenesis Thus, suppression of activated HSCs is of great importance for preventing liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that up to 90% of eukaryotic genomes are transcribed, while the majority of transcripts are lncRNAs, which are a group of transcripts longer than 200 nucleotides but do not encode protein 12 . Despite their poor conservation and low levels of expression compared with protein-coding genes, more and more lncRNAs are reported to get involved in a variety of physiological and pathological processes, such as hepatic fibrosis 19,[24][25][26][27][28] . For instance, lncRNA H19 aggravated cholestatic liver fibrosis either by promoting HSCs activation or by preventing ZEB1-mediated inhibition of epithelial cell adhesion molecule 25,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite their poor conservation and low levels of expression compared with protein-coding genes, more and more lncRNAs are reported to get involved in a variety of physiological and pathological processes, such as hepatic fibrosis 19,[24][25][26][27][28] . For instance, lncRNA H19 aggravated cholestatic liver fibrosis either by promoting HSCs activation or by preventing ZEB1-mediated inhibition of epithelial cell adhesion molecule 25,29 . Yu et al 27 has demonstrated that lncRNA SNHG7 reduced miR-378a-3p and attenuated its control on DVL2, leading to aberrant Wnt/β-catenin activity that contributes to liver fibrotic progression.…”
Section: Discussionmentioning
confidence: 99%